Connected banks and economic policy uncertainty - Cheng, Hua; Gawande, Kishore; Ongena, Steven; Qi, Shusen (Journal of Financial Stability, 2021)
In this paper, we examine the role of political connections in mitigating the detrimental impact of policy uncertainty on banks. Our estimates show that banks are more cautious when facing policy uncertainty, but that the effect is partially alleviated when banks are politically connected. For an increase of one standard deviation in policy uncertainty, connected banks maintain a loss provision to loan volume ratio that is almost seven percent lower compared to their unconnected peers. These findings are robust to a geographical regression discontinuity setting, as well as to a placebo test. Lastly, the mitigating role of political connections is driven mainly by smaller banks and periods of stricter banking regulations.